PENGARUH PROFITABILITAS, LIKUIDITAS TERHADAP STRUKTUR MODAL PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Handriyani Dwilita; Nadiya R Nababan; Julia Meilany Tumenggar; Mutiara Sri Harta S; Finanty Yolanda (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to examine in depth how profitability and liquidity affect the capital structure of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. The research approach used a quantitative method utilizing secondary data in the form of company financial reports. The sample selection technique used in this study was purposive sampling, resulting in 22 sample companies that met the research criteria, which were measured using the Debt to Equity Ratio (DER) indicator. Meanwhile, the independent variables consisted of Return on Equity (ROE) as a representation of profitability and Current Ratio (CR) as a representation of liquidity. The results of the descriptive analysis showed that the average DER of food and beverage sub-sector companies was 8.214, the average ROE was 0.595, and the average CR was 2.619. The correlation test showed that DER had no significant relationship with ROE, but showed a significant negative correlation with CR. Furthermore, the results of the multiple linear regression test indicated that ROE had no significant effect on DER, while CR had a negative effect that was close to significant on DER. The results of this study indicate that liquidity plays a role in capital structure compared to profitability in food and beverage subsector companies in 2021-2024.